NAVIGATING DIGITAL FRONTIER: CONSUMERS’ WILLINGNESS TO PURCHASE FRESH VEGETABLES THROUGH MOBILE COMMERCE IN PAKISTAN - Manan ASLAM; Zhiwen LI; Muneeb Ahmad GUJJAR; Mubashar FAROOQ; Muneeb Ahmad ANSARI; Daniyal HASSAN; Rao Izhar ul HAQ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study seeks to develop understanding of determinants affecting consumers’ buying behavior for fresh vegetables through information and communication technology (ICTs) mainly the use of mobile application in the study area. In this regard, those drivers which trigger consumer’s willingness to purchase these vegetables by using mobile commerce were identified. It might be greatly reduced the intermediate links of vegetable distribution and simplify the food purchasing in people’s daily life. This application of mobile technology would have an enormous potentials in marketers, food industries, farming community, decision makers, and consumers. Enabling consumers more informed about the novel innovative technologies for receiving and sharing information about market trends, prices, and avenues, among the ICTs smart phone applications are usually considered a quick method to approach markets, attain information about agricultural commodities and their prices in an effective and desired manner. In order to assess consumers’ willingness to pay for the fresh produce by using mobile commerce as it is critical to understand factors that affect its consumption. A sample size of 600 respondents including two metropolitan cities of Punjab viz. Lahore and Multan were selected purposively. According to the findings of research, income of the consumer, education of the consumer, distance of fresh vegetable from store outlet/mart, advertisement of fresh vegetables, prices of fresh vegetables, cognition of mcommerce and availability of fresh vegetables were significantly influencing consumers’ willingness to buy fresh vegetables by using mobile commerce whereas taste of fresh vegetables, age of consumer, no use of synthetic pesticide residue on fresh vegetables, availability of produce were affecting non significantly towards consumers willingness to buy fresh vegetables in the study area. There is a dire need to inculcate the importance of technology as well as the benefits of purchasing fresh vegetables to consumers through proper advertisement by employing information and communication (ICTs) gadgets.